La dynamique des représentations : frontières et paysage sociopolitique postclassique des Hautes Terres mayas - Marie Annereau-Fulbert (Ateliers d'Anthropologie)
Ethnohistorical sources from the Guatemala Highlands describe the Post-Classical period, at the dawn of the Spanish conquest, as a period of torment, fuelled by ceaseless conflict between groups that are sociopolitically distinct but have similar languages. And yet they share a common history that is evoked in the form of migration stories and myths. Without questioning the truth of the historical facts that these may illustrate, we will see, thanks to certain passages from the Popol Vuh compiled in the 16th century and other texts from that period, that they served to subjugate several radical moments of rupture with the old world order, by redefining the boundaries of alterity and power relations in relation to a central authority whose identity was also displaced according to circumstances. In this case, questioning the relationship between myth and boundary comes down to examining the relation between myth and politics.